Smacoviridae: a new family of animal-associated single-stranded DNA viruses - Varsani, Arvind; Krupovic, Mart (Archives of virology, 2018)
Smacoviruses have small (∼2.3-2.9 kb), circular single-stranded DNA genomes encoding rolling circle replication-associated proteins (Rep) and unique capsid proteins. Although smacoviruses are prevalent in faecal matter of various vertebrates, including humans, none of these viruses have been cultured thus far. Smacoviruses display ∼45% genome-wide sequence diversity, which is very similar to that found within other families of circular Rep-encoding single-stranded (CRESS) DNA viruses, including members of the families Geminiviridae (46% diversity) and Genomoviridae (47% diversity). Here, we announce the creation of a new family Smacoviridae and describe a sequence-based taxonomic framework which was used to classify 83 smacovirus genomes into 43 species within six new genera, Bovismacovirus (n=3), Cosmacovirus (n=1), Dragsmacovirus (n=1), Drosmacovirus (n=3), Huchismacovirus (n=7), and Porprismacovirus (n=28). As in the case of genomoviruses, the species demarcation is based on the genome-wide pairwise identity, whereas genera are established based on the Rep amino acid sequence identity coupled with strong phylogenetic support. A similar sequence-based taxonomic framework should guide the classification of an astonishing diversity of other uncultured and currently unclassified CRESS DNA viruses discovered by metagenomic approaches.